2010
DOI: 10.1084/jem.20100086
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid cells, BAFF, and IFN-γ establish an inflammatory loop that exacerbates autoimmunity in Lyn-deficient mice

Abstract: Autoimmunity is traditionally attributed to altered lymphoid cell selection and/or tolerance, whereas the contribution of innate immune cells is less well understood. Autoimmunity is also associated with increased levels of B cell–activating factor of the TNF family (BAFF; also known as B lymphocyte stimulator), a cytokine that promotes survival of self-reactive B cell clones. We describe an important role for myeloid cells in autoimmune disease progression. Using Lyn-deficient mice, we show that overproductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
143
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 96 publications
(152 citation statements)
references
References 59 publications
7
143
0
2
Order By: Relevance
“…Different SFKs have also been shown to recognize different substrates (43), and this combined with the sequential regulation of Hck and Src may explain why different SFK family members play distinct roles within a single cell type. A recent publication by Keck et al (44) demonstrated that the ablation of Lyn in murine macrophages actually resulted in increased TNF, IL-6, and IFNa/b, and there is exacerbated autoimmunity in these mice (45). Thus, the lack of effect in the triple SFK knockouts may be because of not only functional redundancy, but may also be attributed to the kinases having both positive and negative effects on cytokine production.…”
Section: Discussionmentioning
confidence: 99%
“…Different SFKs have also been shown to recognize different substrates (43), and this combined with the sequential regulation of Hck and Src may explain why different SFK family members play distinct roles within a single cell type. A recent publication by Keck et al (44) demonstrated that the ablation of Lyn in murine macrophages actually resulted in increased TNF, IL-6, and IFNa/b, and there is exacerbated autoimmunity in these mice (45). Thus, the lack of effect in the triple SFK knockouts may be because of not only functional redundancy, but may also be attributed to the kinases having both positive and negative effects on cytokine production.…”
Section: Discussionmentioning
confidence: 99%
“…Lungs, liver, skin, and kidneys were processed and stained with H&E by the UCSF Pathology core. Kidneys were snap-frozen in optimal cutting temperature compound and 5-μm sections were stained for C3 as previously described (2). For detection of ANA, sera were diluted 1:40 and used for detection of ANAs on fixed Hep-2 ANA slides (Bio-Rad Laboratories) and revealed with FITC-conjugated goat anti-mouse IgG (Jackson ImmunoResearch Laboratories, Inc.).…”
Section: Methodsmentioning
confidence: 99%
“…Recent findings from our laboratory demonstrate that (i) in vitro, lyn −/− DCs secrete high levels of cytokines associated with autoimmunity; (ii) in vivo, the increase in serum levels of some of these cytokines precedes the generation of autoantibodies; and (iii) deletion of Lyn in myeloid cells in lyn −/− rag-1 −/− doublemutant mice causes myeloid expansion, suggesting that the myeloproliferative phenotype observed in lyn −/− mice is only partly dependent on B-cell-mediated autoimmunity (2). Hence, we hypothesized that the autoimmunity in lyn −/− mice is not only due to defects in B cells, but also to the hyperactivation of cells from myeloid and dendritic cell lineages.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…TFH, in turn, produces BAFF, and this may enhance the survival and selection of high-affinity B cells (18). Furthermore, activated T cells are also responsive to BAFF, releasing interferon-γ that amplifies autoimmune effector responses (19). The ability of BAFF inhibition to regulate plasma cells that arise either from naive autoreactive B cells or from the GC has not been fully explored in spontaneous models of SLE.…”
Section: Micementioning
confidence: 99%